2009
DOI: 10.1152/ajpregu.00281.2009
|View full text |Cite
|
Sign up to set email alerts
|

Absorption kinetics are a key factor regulating postprandial protein metabolism in response to qualitative and quantitative variations in protein intake

Abstract: We have previously demonstrated that increasing the habitual protein intake widened the gap in nutritional quality between proteins through mechanisms that are not yet fully understood. We hypothesized that the differences in gastrointestinal kinetics between dietary proteins were an important factor affecting their differential response to an increased protein intake. To test this hypothesis, we built a 13-compartment model providing integrative insight into the sequential dynamics of meal nitrogen (Nm) absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 80 publications
(156 reference statements)
3
45
0
Order By: Relevance
“…In addition to digestibility issues, it was reported that the dietary protein-derived AAs from the plant-based proteins soy and wheat are more readily converted to urea when compared with the ingestion of milk proteins (56)(57)(58)(59). This would ultimately lower the potential of these plant-based protein sources to stimulate the skeletal muscle anabolic response.…”
Section: Protein Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to digestibility issues, it was reported that the dietary protein-derived AAs from the plant-based proteins soy and wheat are more readily converted to urea when compared with the ingestion of milk proteins (56)(57)(58)(59). This would ultimately lower the potential of these plant-based protein sources to stimulate the skeletal muscle anabolic response.…”
Section: Protein Qualitymentioning
confidence: 99%
“…As described previously, plant-based protein sources are generally lower in lysine and/or methionine than are animal-based protein sources (Table 3, Figure 2). This may impair the postprandial MPS response after the ingestion of plant-based protein sources when compared with animal-based proteins (56)(57)(58)(59). Thus, similar to leucine fortification, it may be hypothesized that adding lysine and/or methionine to plant-based proteins is a useful strategy to improve their anabolic properties.…”
Section: Strategies To Augment the Anabolic Properties Of Plant-basedmentioning
confidence: 99%
“…The model calculations are fairly complex but allow one to predict the kinetics of dietary nitrogen in the body (Juillet et al, 2006). Both the amino acid profi le of the protein and the kinetics of amino acid delivery to the blood can affect the postprandial splanchnic and peripheral uptake of amino acid in humans (Deglaire et al, 2009b;Fouillet et al, 2000Fouillet et al, , 2001Fouillet et al, , 2002bFouillet et al, , 2003Fouillet et al, , 2009Juillet et al, 2008). Increasing protein intake increases splanchnic catabolic use while splanchnic catabolic use and peripheral anabolic use are inversely affected (Fouillet et al, 2009).…”
Section: Results For Ileal Digestibility and Nppu Of Protein Sourcesmentioning
confidence: 99%
“…. , δ; r ≤ v) are given by: (22) and each submatrix indicated as 0 in Expression (21), which is located in the r th row and vth column of matrix K , has n v rows and n r columns, while all its elements are zeros. It may also possible that one or more of the submatrices denoted as M r,v (r > v if r ≤ f ) may be a matrix r × v, whose elements are all zeros.…”
Section: The Expression Of Matrix K In the Submatricesmentioning
confidence: 99%